Bioremediation of polycyclic aromatic hydrocarbons from an aged contaminated agricultural soil using degrading bacteria and soil amendments. Issue 4 (15th June 2022) - Liu, Binxu; Ge, Wei; Liu, Xiuchu; Zhang, Xiaomei; Chen, Qinghua; Wu, Juan; Li, Zhiying; Chai, Chao
Abstract: The combined effects of degrading bacteria ( Paracoccus sp. LXC), humic acid (HA), and soil amendments, including chicken manure, biochar, and wormcast, were investigated through 84 d of incubation in order to improve the remediation of polycyclic aromatic hydrocarbon (PAH) in aged contaminated agricultural soil. PAH concentrations and dissipation kinetics were analyzed, and the biomass and communities of microorganisms and soil enzyme activities were examined to clarify the possible mechanism. The highest removal efficiency of PAHs was 42.1% when treated with Paracoccus sp. LXC combined with biochar and HA. PAH dissipation was consistent with the first-order kinetics model and the half-life of PAHs decreased from 2323.3 d in the natural attenuation to 103–277 d in the amended microcosms. Soil amendments and HA promoted the development of PAH-degrading bacteria and diversity of bacterial communities in soil but not that of fungi. The removal efficiency of PAHs was positively correlated with the density of PAH-degrading bacteria and soil urease (Ure), dehydrogenase (Deh), and manganese-dependent peroxidase (Mnp) activities ( r = 0.824–0.941, p < .01). The Paracoccus sp. LXC apparently removed 2–4-ring PAHs, and biochar and wormcast were effective in removing 2–4-ring and 5–6-ring PAHs, respectively. The combined bioremediation strategy using degrading bacteria with soil amendments and HA has high potential for PAH removal in aged contaminated agricultural soil and the possible mechanism was the combination of bioaugmentation with Paracoccus sp. LXC and biostimulation with HA and soil amendments.